1994
DOI: 10.3354/dao018149
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of oxidase-negative Aeromonas salmonicida from diseased turbot Scophthalmus maximus

Abstract: The first outbreak of dlsease due to an atyplcal Aeromonas salmonicida among turbot Scophthalmus maximus (L.) in Denmark is reported. The causal organism was oxidase-negative, non-pigmented, and slow-growing. Additionally it differed from the typical strains in a number of biochemical characters. The mortality among turbot in the farm was high but was responsive to antlmlcrobial therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 12 publications
4
44
0
Order By: Relevance
“…Both of the experimental fish pathogen (A. salmonicida and Y. ruckeri) were Gram negative when staining was performed using Gram staining method (Buck, 1982). Several studies have suggested that the A. salmonicida (Pedersen et al, 1994;Gudmundsdottir, 1998;Schmidt et al, 2000) and Y. ruckeri are gram negative fish bacteria (Tinsley et al, 2011;Verner-Jeffreys et al, 2011;Welch et al, 2011) which are reliable with the present results. The oxidase test was used to identify the presence of respiratory enzymes, cytochrome oxidase in the bacterial isolates.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Both of the experimental fish pathogen (A. salmonicida and Y. ruckeri) were Gram negative when staining was performed using Gram staining method (Buck, 1982). Several studies have suggested that the A. salmonicida (Pedersen et al, 1994;Gudmundsdottir, 1998;Schmidt et al, 2000) and Y. ruckeri are gram negative fish bacteria (Tinsley et al, 2011;Verner-Jeffreys et al, 2011;Welch et al, 2011) which are reliable with the present results. The oxidase test was used to identify the presence of respiratory enzymes, cytochrome oxidase in the bacterial isolates.…”
Section: Discussionsupporting
confidence: 86%
“…Like oxidase test, A. salmonicida give positive reaction with catalase test. A Positive oxidase and catalase test of A. salmonicida were recoded from turbot fish farm in Denmark (Pedersen et al, 1994;Dalsgaard and Madsen, 2000). The studied A. salmonicida was observed as cytochrome oxidase positive like other research.In contrast, negative oxidase test for Y. ruckeri was recorded from the rainbow trout farm in Spain (Fouz et al, 1990).…”
Section: Discussionmentioning
confidence: 62%
“…Atypical A. salmonicida has been isolated from a number of marine fish species, such as sable fish Anoplopoma fimbria (Evelyn 1971), Atlantic cod (Cornick et al 1984), marine sand eel Ammodytes lancea (Dalsgaard & Paulsen 1986), Pacific herring Clupea harengus pallasi (Traxler & Bell 1989), flounder Platichthys flesus (Wiklund & Bylund 1991), goldsinny (Frerichs et al 1992) and turbot Scophthalmus maximus (Pedersen et al 1994). Typical A. salmonicida (subsp.…”
Section: Introductionmentioning
confidence: 99%
“…The farming of these 3 species has already encountered problems with several bacterial infections, such as vibrio infections (Vibrio anguillarum and Vibrio vulnificus) and atypical Aeromonas salmonicida infections (Mellergaard & Dalsgaard 1987, Noga et al 1990, Biosca et al 1991, Fouz et al 1992, 1995, Austin et al 1993, Liewes & Haenen 1993, Pedersen et al 1994, Grisez et al 1996, Larsen & Pedersen 1996, Bergh et al 1997, Olsson et al 1998, Bricknell et al 1999, 2000, Dalsgaard et al 1999, Gatesoupe et al 1999.…”
Section: Introductionmentioning
confidence: 99%